ПРИМЕНЕНИЕ ПРОГНОЗНЫХ МЕТОДОВ ДЛЯ УПРАВЛЕНИЯ ПОЛУПРОВОДНИКОВЫМИ ПРЕОБРАЗОВАТЕЛЯМИ В СИСТЕМЕ ЭЛЕКТРОСНАБЖЕНИЯ - Сокол, Е.И.; Гончаров, Ю.П.; Замаруев, В.В.; Ивахно, В.В.; Кривошеев, С.Ю.; Лобко, А.В.; Безъязычный, А.В.; Войтович, Ю.С.; Стысло, Б.А.; Дзюндзя, И.В. (Інститут електродинаміки НАН України, Київ, 2014)
Offered to suppress resonance phenomena using active filters or other converters with active filtering functions using predictive management principles. Presents the developed procedure for the synthesis of discrete frequencies filter. References 5, figures 3.